Ceramic Firing Temperature Trajectory Monitoring System on IoT-Based Gas Furnace: English - I Wayan Oka Prayasa; Agus Putu Abiyasa; I Putu Angga Kristyawan (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2023)
This study introduces a novel system where a conventional ceramic furnace is upgraded with IoT capabilities, specifically utilizing NodeMCU and a thermocouple sensor. The integrated system enables real-time temperature monitoring, facilitating the correction of firing trajectory errors in the ceramic firing process. The sensors reading minimizes errors by detecting temperature changes with a maximum deviation of -2.5 °C and a minimum deviation of -1 °C. The average error ranges from 1.81% to 3.79%. The collected data is seamlessly transmitted to Google Spreadsheet for online monitoring. This comprehensive solution not only minimizes recording errors but also ensures the quality of final ceramic products by preventing issues such as cracks, breaks, black cores, and non-uniform sizes. The incorporation of NodeMCU, thermocouple sensors, and online monitoring represents a significant technological leap in optimizing ceramic firing processes for heightened precision and efficiency.